Diabetic mice exhibited a peculiar alteration in body composition with exaggerated ectopic fat deposition after muscle injury due to anomalous cell differentiation. Issue 2 (2nd June 2015) - Mogi, Masaki; Kohara, Katsuhiko; Nakaoka, Hirotomo; Kan‐no, Harumi; Tsukuda, Kana; Wang, Xiao‐Li; Chisaka, Toshiyuki; Bai, Hui‐Yu; Shan, Bao‐Shuai; Kukida, Masayoshi; Iwanami, Jun; Miki, Tetsuro; et al.
Abstract: Background: Sarcopenic obesity, age‐related muscle loss, which is compensated by an increase in fat mass, impairs quality of life in elderly people. Although the increase in intramuscular fat is associated with decreased insulin sensitivity and increased metabolic risk factors, the origin of diabetes‐associated intramuscular fat has not been elucidated. Here, we investigated intramuscular fat deposition using a muscle injury model in type 2 diabetic mice. Methods: Male 8‐week‐old C57BL/6 and 8‐week‐old and 26‐week‐old KKAy underwent intramuscular injection of cardiotoxin (Ctx) (100 μL/10 μM) into the tibialis anterior (TA) muscles. After 2 weeks, the muscles were removed and evaluated. Results: KKAy exhibited impaired muscle regeneration and ectopic fat deposition. Such impairment was more marked in older KKAy. These changes were also observed in another diabetic mouse model, db/db and diet‐induced obese mice but not in streptozocin‐induced diabetic mice. Deposited fat was platelet‐derived growth factor (PDGF) receptor alpha positive and its cytoskeleton was stained with Masson's trichrome, indicating it to be of fibro‐adipocyte progenitor cell origin. Expression of a myogenic marker, myoD, was lower and that of PDGF receptor alpha and CCAAT/enhancer binding protein (CEBP) alpha was higher in Ctx‐injured TA of KKAy compared with that of C57BL/6. Peroxisome proliferator‐activated receptor γ (PPARγ) was highly expressed in fat‐forming lesions in older KKAy. Treatment with all‐trans retinoic acid prevented the formation of intramuscular fat; however, treatment with GW9662, a PPARγ antagonist, increased the fibrotic change in muscle. Conclusions: Diabetic mice showed impaired muscle regeneration with fat deposition, suggesting that diabetes may enhance sarcopenic obesity through a mechanism involving anomalous fibro‐adipocyte progenitor cell differentiation.